Growth and survival rate of SHELL DARA (Anadara granosa) MUD ON DIFFERENT THICKNESS - Wahyu Subarkah; Rusliadi '; Usman Muhammad Tang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Virgin shells of species (Anadara granosa) is one of the fisheries resources of economically valuable species bivalve mollusks. Inidimaksudkan research for sustainable management of shellfish resources in terms of virgin ecological and economic aspects which took place in February-March 2013 in the waters of the Village District Commander King Concong Affairs Indragiri Hilir Riau Province. This study aims to assess the potential and development of shellfish resources and determine the strategic direction for the cultivation and development of these resources. Research include: (a) the survival rate (b) growth of mussel shells, (c) Analysis of resource development strategy. The results showed that the ecological, shellfish cultivation virgin menurupan promising business for the fishermen. Cultivation method using board height 10 cm, height 20 cm board size and board size 30 cm high. nets are used to measure diamaeter 1 cm seed in stocking with an average length of 2.25 cm and an average weight of 2.47 grams of 450 tails. The result is the growth length of 2.25 cm to 3.08 cm. Growth of 2.48 weight, gram to 5.00 gram.Keywords: Shells virgin, Ecology, seeds, growthPENDAHULUANKerang darah